Paper things - Jacobson, Jennifer, 1958- (Candlewick Press, 2015)
When Ari's mother died four years ago, she had two final wishes: that Ari and her older brother, Gage, would stay together always, and that Ari would go to Carter, the middle school for gifted students. So when nineteen-year-old Gage decides he can no longer live with their bossy guardian, Janna, Ari knows she has to go with him. But it's been two months, and Gage still hasn't found them an apartment. He and Ari have been "couch surfing," staying with Gage's friend in a tiny apartment, crashing with Gage's girlfriend and two roommates, and if necessary, sneaking into a juvenile shelter to escape the cold Maine nights. But all of this jumping around makes it hard for Ari to keep up with her schoolwork, never mind her friendships, and getting into Carter starts to seem impossible. Will Ari be forced to break one of her promises to Mama? Told in an open, authentic voice, this nuanced story of hiding in plain sight may have readers thinking about homelessness in a whole new way.